Psychosocial coping strategies in cancer patients - Šprah, Lilijana (Radiology and oncology (Ljubljana), 2004)
Background. The aim of this review is to present common psychosocial problems in cancer patients and their possible coping strategies. Cancer patients are occupied with many psychosocial problems, which are only partially related to their health state and medical treatments. They are faced with a high social pressure, based on prejudices and stereotypes of this illness. The review presents the process of confrontation with the cancer diagnosis and of managing the psychological consequences of cancer. The effects of specific coping styles, psychosocial interventions and a social support on initiation, progression and recurrence of cancer are also described. Conclusions. Althoughsome recent meta-analysis could not provide scientific evidence for the association befween coping strategies and the cancer initiation, the progression or the recurrence (neither have studies rejected the thesis of association), the therapeutic window for the psychosocial intervention is still wide and shows an important effect on the quality of lives of many cancer patients.
Keywords: Bolezen, napredovanje; Disease Progression; Neoplasms; Novotvorbe; onkologija; Ponovitev; psihosocialne težave; Psychology; rak (medicina); Recurrence; Social Support; Socialna pomoč; soočanje; tumor